Overexpression of a MYB Family Gene, OsMYB6, Increases Drought and Salinity Stress Tolerance in Transgenic Rice - Tang, Yuehui; Bao, Xinxin; Zhi, Yuling; Wu, Qian; Guo, Yaru; Yin, Xuhui; Zeng, Liqin; Li, Jia; Zhang, Jing; He, Wenlong; Liu, Weihao; Wang, Qingwei; et al. (Frontiers in Plant Science, 2019)
MYB transcription factors have been demonstrated to play key regulatory roles in plant growth, development and abiotic stress response. However, knowledge concerning the involvement of rice MYB genes in salinity and drought stress resistance are largely unknown. In the present study, we cloned and characterized the OsMYB6 gene, which was induced by drought and salinity stress. Subcellular localization of OsMYB6-YFP fusion protein in protoplast cells indicated that OsMYB6 was localized in the nucleus. Overexpression of OsMYB6 in rice did not suggest a negative effect on the growth and development of transgenic plants, but OsMYB6-overexpressing plants showed increased tolerance to drought and salt stress compared with wild-type plants, as are evaluated by higher proline content, higher CAT and SOD activities, lower REL and MDA content in transgenic plants under drought and salt stress conditions. In addition, the expression of abiotic stress-responsive genes were significantly higher in OsMYB6 transgenic plants than that in wild-type plants under drought and salt stress conditions. These results indicate that OsMYB6 gene functions as a stress-responsive transcription factor which plays a positive regulatory role in response to drought and salt stress resistance, and may be used as a candidate gene for molecular breeding of salt-tolerant and drought-tolerant crop varieties.